Further notes on the genus Ocellarnaca Gorochov, 2004 (Orthoptera: Gryllacrididae) from China - Shi, Fu-Ming; Zhu, Qi-Di (Zootaxa, 2021)
The paper reports three new species of the genus Ocellarnaca Gorochov, 2004 (Orthoptera: Gryllacrididae) from China, i.e. Ocellarnaca brachyptera sp. nov., Ocellarnaca nigrofemora sp. nov., Ocellarnaca nigra sp. nov. The type specimens are deposited in the Museum of Hebei University, Baoding 071002, China.